Physical activity status prevents symptoms of long covid: Sulcovid-19 survey - Juliana Quadros Santos Rocha; Eduardo Lucia Caputo; Yohana Pereira Vieira; Max dos Santos Afonso; Suele Manjourany Silva Duro; Mirelle de Oliveira Saes (BMC, 2023)
Abstract Background Physical activity is indicated as a treatment for Long COVID, but prevention is unknown. This study aimed to investigate the relationship between physical activity (PA) before and after acute SARS-Cov-2 infection and the presence of Long COVID symptoms in adults. Methods We used data from the Sulcovid-19, a longitudinal study carried out with individuals who were infected by SARS-Cov-2 between December/2020 and March/2021. Participants were asked about 19 symptoms commonly associated with long COVID. Three PA variables were built, as follows: (1) remained inactive; (2) became inactive; (3) remained active. Results 2.919 people were interviewed. The prevalence of individuals who had at least one symptom of Long COVID is 48.3% (95%CI 46.5-51.1). Our results showed that 71.8% (95%CI 70.1-73.4) of the individuals remained inactive, 14.9% (95%CI 13.6-16.2) became inactive and 13.3% (95% CI 12.1-14.6) remained active. The likelihood of experiencing long COVID symptoms was reduced in the musculoskeletal (PR 0.70; 95%CI 0.49-0.99), neurological (PR 0.61; 95%CI 0.43-0.88), and respiratory (PR 0.58; 95%CI 0.35-0.96) systems in those who remained active. In addition, the likelihood of experiencing Long COVID symptoms was 7% less in those who remained active. Conclusions Continuous PA practice showed important protection effect for Long COVID symptoms in adults.